2022
DOI: 10.3390/ijms23136977
|View full text |Cite
|
Sign up to set email alerts
|

Immunorthodontics: Role of HIF-1α in the Regulation of (Peptidoglycan-Induced) PD-L1 Expression in Cementoblasts under Compressive Force

Abstract: Patients with periodontitis undergoing orthodontic therapy may suffer from undesired dental root resorption. The purpose of this in vitro study was to investigate the molecular mechanisms resulting in PD-L1 expression of cementoblasts in response to infection with Porphyromonas gingivalis (P. gingivalis) peptidoglycan (PGN) and compressive force (CF), and its interaction with hypoxia-inducible factor (HIF)-1α molecule.: The cementoblast (OCCM-30) cells were kinetically infected with various concentrations of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…An immortalized murine cementoblast (OCCM-30) cell line [ 31 , 32 ] was kindly provided by Prof. M. Somerman (Laboratory of Oral Connective Tissue Biology, NIH, Bethesda, MD, USA). OCCM-30 cells were cultured in α-minimal essential medium (α-MEM) (11095-080, Gibco, Gaithersburg, MA, USA), supplemented with 10% ( v / v ) fetal bovine serum (FBS) (10270-106, Gibco) and 1% Penicillin/Streptomycin (P/S) (15140-122, Gibco) in 6-wells cell culture plates (657160, Greiner bio-one, Frickenhausen, Germany) at 37 °C humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…An immortalized murine cementoblast (OCCM-30) cell line [ 31 , 32 ] was kindly provided by Prof. M. Somerman (Laboratory of Oral Connective Tissue Biology, NIH, Bethesda, MD, USA). OCCM-30 cells were cultured in α-minimal essential medium (α-MEM) (11095-080, Gibco, Gaithersburg, MA, USA), supplemented with 10% ( v / v ) fetal bovine serum (FBS) (10270-106, Gibco) and 1% Penicillin/Streptomycin (P/S) (15140-122, Gibco) in 6-wells cell culture plates (657160, Greiner bio-one, Frickenhausen, Germany) at 37 °C humidified atmosphere with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The immortalized murine cementoblast cell line (OCCM-30) [ 28 , 29 ] (generously provided by Prof. J. Deschner and Dr. M. Nokhbehsaim, Department of Periodontology, University of Bonn, Germany) was plated with a seeding density of 1 × 10 6 cell/well and maintained at 37 °C in a humidified atmosphere with 5% CO 2 in air. OCCM-30 cells were cultured in the regular growth medium α-MEM (Gibco, Gaithersburg, MA, USA), supplemented with 10% ( v / v ) heat-inactivated fetal bovine serum (FBS) (Gibco) and 1% penicillin/streptomycin (Gibco) in 6-well plates (Greiner bio-one, Frickenhausen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated to be up-regulated upon immune activation conditions, such as inflammations [ 83 ]. In recent studies, we identified for the first time that PD-L1 is induced and constantly expressed on murine cementoblasts in response to compression and hypoxia, simulating orthodontic-force-induced microenvironmental changes [ 84 , 85 ]. In detail, the recent data revealed that the application of a compressive force at a magnitude of 2.4 gf/cm 2 enhances the PD-L1 expression in cementoblasts.…”
Section: Pd-l1 and Oiirrmentioning
confidence: 99%
“…When cementoblasts were subjected to a modified compression, they expressed stable PD-L1, which in turn may facilitate their antigenic escape from immune surveillance. In addition, it was revealed that HIF-1α plays an pivotal role in the PD-L1 modulation [ 84 ]. Another very recent study conducted by our group showed that long-term exposure to hypoxic conditions augmented PD-L1 expression on cementoblasts [ 85 ].…”
Section: Pd-l1 and Oiirrmentioning
confidence: 99%